HUBUNGAN PENGETAHUAN, SIKAP DENGAN KESIAPSIAGAAN TENAGA KESEHATAN PUSKESMAS DALAM MENGHADAPI BENCANA BANJIR DI KABUPATEN SIDENRENG RAPPANG - Rini Mustamin; Wachyudi Muchsin (Stikes Graha Edukasi Makassar, 2022)
Destination:. namely knowing the relationship between knowledge and attitudes with the preparedness of health workers in the Community Health Center in dealing with floods in Sidrap Regency. Research design: namely an analytical survey with a cross-sectional study approach through the use of quantitative methods. The study population, namely all health workers at the Bilokka Health Center, Amparita Health Center and Empagae Health Center in Sidenreng Rappang Regency, were 96 people as samples. Data obtained by interview, observation, and questionnaires. The analysis was carried out using the Pearson Chi Square test and logistic regression. The data were analyzed using the SPSS 17 program. The results of the study showed that statistically the variables of knowledge and attitudes had a significant relationship with the health workers at the Bilokkka Health Center, Amparita Health Center and Empagae Health Center in Sidenreng Rappang Regency. Conclusion:. the preparedness of Health Center health workers in Sidenreng Rappang Regency (Bilokka Health Center, Amparita Health Center and Empagae Health Center) in dealing with flood disasters in Sidenreng Rappang Regency is included in the fairly prepared category in terms of flood disaster knowledge, most of them are quite good. Sidenreng Rappang has a positive attitude. Suggestions The need for health workers to increase their knowledge and actions regarding preparedness for flood disasters through various means such as through books or guidelines, the internet, seminars, conferences and training or simulations regarding flood disaster management and handling of emergencies facilitated by the Management of the Sidenreng Rappang District Health Office and through collaboration with related parties